The effect of the SCAMPER strategy on the achievement of fifth-grade students in science (Journal of the College of Basic Education, 2022)
The aim of the research is to know (the effect of the SCAMPER strategy on the achievement of fifth-grade students in science), and to verify the goal of the research, the following null hypothesis was formulated:- There is no statistically significant difference at the significance level (0.05)between the average scores of the students who studied according to the SCAMPER strategy and the average scores of the students who studied according to the usual method in the achievement test.The researcher adopted the experimental design with partial control, which includes two groups, one of them is an experimental one taught according to the SCAMPER strategy, and the other is a control one that is taught according to the usual method. The researcher chose Al-Shumukh Elementary School for Girls from among the basic and primary schools affiliated to the Baghdad Education Directorate / Al-Rusafa Secondary School to represent the research sample,, where the total number of female students in the school was (150) students divided into four divisions (A, B, C, D) respectively (39, 37, 38, 36). Division (C) was chosen by random assignment to represent the experimental group and Division (D) to represent the control group of (74) female students. After statistically repetitive students were excluded from the experiment data because they had previous cognitive experience in the topics that will be studied during the experiment period, the final number of the sample became (60) students, with (30) female students for the experimental group and (30) A student of the control group.The two groups were rewarded in the variables: (chronological age of the students, calculated in months, intelligence test, prior knowledge, parents’ academic achievement, decision making) and the experiment was conducted in the first semester of the academic year (2021-2022).The researcher used the statistical program (SPSS), including (t-test for two independent samples, chi-square test - Kewder-Richardson equation 20 - Correlation coefficient Point Pacerial, coefficient of discrimination of objective paragraphs).In light of this, the results revealed that there were statistically significant differences in favor of the experimental group in the achievement test for science with a significant effect.